2011
DOI: 10.1063/1.3587236
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of Na1/2Bi1/2TiO3-x%BaTiO3 single crystals as a function of temperature and composition

Abstract: Articles you may be interested inChemical and structural effects on the high-temperature mechanical behavior of (1−x)(Na1/2Bi1/2)TiO3-xBaTiO3 ceramics J. Appl. Phys. 117, 134110 (2015); 10.1063/1.4916784Anisotropy of ferroelectric behavior of (1 − x)Bi1/2Na1/2TiO3-xBaTiO3 single crystals across the morphotropic phase boundary J. Appl. Phys. 116, 044111 (2014) A Raman spectroscopic study of Na 1/2 Bi 1/2 TiO 3 -x%BaTiO 3 (NBT-x%BT) single crystals with x ¼ 0 and 5.6 has been performed as a function of temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 42 publications
(62 reference statements)
8
41
0
Order By: Relevance
“…The spectrum of NBT is in general very similar and in good agreement with the already published work [11,[76][77][78][79], where it was assigned a total of 13 Ramanactive modes (Γ R3c = 4A 1 + 9E) [78] that similar main regions in the spectrum can be detected [79]. It can be seen that all Raman bands are relatively broad which can be related to a possible disorder at A-site due to the random distribution of Na/Bi cations.…”
Section: At Room Temperaturesupporting
confidence: 75%
“…The spectrum of NBT is in general very similar and in good agreement with the already published work [11,[76][77][78][79], where it was assigned a total of 13 Ramanactive modes (Γ R3c = 4A 1 + 9E) [78] that similar main regions in the spectrum can be detected [79]. It can be seen that all Raman bands are relatively broad which can be related to a possible disorder at A-site due to the random distribution of Na/Bi cations.…”
Section: At Room Temperaturesupporting
confidence: 75%
“…4(a). Three main active modes were perceived in the pure BNBTNb-SZ ceramics from 100 to 700 cm −1 , which were identical to other BNT-based ceramics [49][50][51][52][53]. The Raman-active mode (A 1 ) observed around 150 cm −1 is related to the vibrations of an A-site perovskite structure which comprises of A-site cations Bi, Na, Ba, and Sr.…”
Section: Resultsmentioning
confidence: 85%
“…15,[20][21][22][23][24] Due to challenges of intrinsic broadening and overlapping of phonon modes in the assignment of mode symmetries, structural analysis thus relies on analyzing soft-mode or hard-mode behavior as a function of composition, pressure or temperature. 15,[21][22][23][24] Other studies in NBT-BT 25 and NBT-SrTiO 3 24 generally confirmed that transitions involving the ferroelectric behavior are related to subtle local structural distortions and phase coexistence.…”
Section: As Well Asmentioning
confidence: 77%